Characterization and molecular typing of Escherichia coli isolated from Ulam - Nur Atiqah, Aminudin; Nurul ‘Azyyati, Sabri; Lee, Chin Mei (AIP Publishing, 2025)
Ulam refers to a variety of plants that are rich in nutrients and possess wound-healing and medicinal properties. Studies have shown that ulam have antioxidant, anti-inflammatory and antihypertensive properties. Known for its unique taste and aromatic qualities, ulam is often used in traditional medicine and Malay cuisine. Ulam is commonly consumed raw in Malaysia. Raw vegetables may possess microbial contamination risk. Escherichia coli is one of the most prevalent foodborne pathogens, capable of causing serious gastrointestinal illness. Despite the widespread consumption of ulam, there are limited studies on microbial risk assessment on the consumption of raw ulam. Therefore, the objectives of the present study were to isolate E. coli from ulam raja (Cosmos caudatus), pegaga (Centella asiatica) and daun kaduk (Piper sarmentosum), to identify the isolated E. coli using Gram staining and biochemical tests and to differentiate E. coli at the strain level through REP-PCR and its fingerprint analysis. Ulam samples were collected from wet market in Kuantan and the samples were subjected for enrichment before isolation. A total of 54 isolates were obtained and were identified by Gram staining and biochemical tests. Of the 54 isolates, 22 isolates were confirmed as E. coli. These isolates were then subjected to REP-PCR. Eight distinct PCR fingerprints were successfully identified. These results suggest that these traditional ulam vegetables, which are frequently consumed raw, could be contaminated with E. coli, posing potential health risks to consumers. The results of the present study highlighted the need for improved hygiene practices in handling and consuming raw vegetables to reduce microbial contamination.